Tržna naravnanost podjetij v Sloveniji - realnost ali fikcija? - Snoj, Boris (Akademija MM, 1998)
According to the results of the representative ACE funded international research project "The effect of the privatisation and foreign direct investment on the marketing of enterprises in Central and Eastern Europe" (1995-1997), wich included all the companies in Slovenia with more than 20 employees, different managerial orientations exist in business activities of the companies in Slovenia. It is obvious that mental orientations, which are not market oriented, are prevailing. Research results also indicate that the companies often aren't market oriented, despite the fact that they operate in very competitive and change oriented environment. As the matter of fact such environment tends to eliminate rigid, less capable participants. Almost one half of chief executive officers of the companies included in research is dissatisfied with the degree of market orientation of their enterprises. As to the result of the research the most important obstacles in the implementation of market orientation are "restricted financial sources" and "past habits". The dilemma exists wether present business orientations of the companies interviewed serve as suitable basis for the transition processes of Slovenian economy. Therefore it would be usefull to continue with such research in order to build the data bases for the on going analysis of the business orientation of companies in Slovenia and its impact on their performance.
Keywords: corporation; marketing; podjetje; Slovenia; Slovenija; trženje; tržno gospodarstvo